2020
DOI: 10.1109/access.2020.3014615
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Mobile Forensic Investigation Process Models

Abstract: Mobile Forensics (MF) field uses prescribed scientific approaches with a focus on recovering Potential Digital Evidence (PDE) from mobile devices leveraging forensic techniques. Consequently, increased proliferation, mobile-based services, and the need for new requirements have led to the development of the MF field, which has in the recent past become an area of importance. In this article, the authors take a step to conduct a review on Mobile Forensics Investigation Process Models (MFIPMs) as a step towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 118 publications
1
37
0
1
Order By: Relevance
“…The method employed with their respective processes is further highlighted in Figure 2. This method, adapted a design science research approach, as explored in similar studies [12][13][14]. The topic for the present study was selected using questions concerning the main subject of the research and considering the background of the topic of focus.…”
Section: Methodsmentioning
confidence: 99%
“…The method employed with their respective processes is further highlighted in Figure 2. This method, adapted a design science research approach, as explored in similar studies [12][13][14]. The topic for the present study was selected using questions concerning the main subject of the research and considering the background of the topic of focus.…”
Section: Methodsmentioning
confidence: 99%
“…Twitch is a proprietary and closed-source software, which means knowledge of its implementation (such as source code, programming language used, and engineering design employed) is not publicly available. Therefore, we developed a methodology based on blackbox testing principles for this study [46,47]. This methodology aims to identify forensically relevant streaming functions of Twitch, prepare test-cases for their execution, and list possible evidences of execution of each test-case that are expected to be identified and extracted during forensic analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Twitch is a proprietary and closed‐source software, which means knowledge of its implementation (such as source code, programming language used, and engineering design employed) is not publicly available. Therefore, we developed a methodology based on black‐box testing principles for this study [46,47].…”
Section: Methodsmentioning
confidence: 99%
“…In the past, several authors identified several challenges in digital investigation processes [73], [166]- [172], mainly related to the chain of custody preservation, the growth of the data to be processed, and privacy and ethical issues when collecting such data. In addition, our research methodology identified several literature reviews which discussed the challenges and limitations of forensic frameworks.…”
Section: A Forensic Framework and Process Modelsmentioning
confidence: 99%